Mobile usage behavior-focusing on smartphone usage addiction among youth (15–24 years of age) - Teguh Pribadi; Andi Susanto (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: Fast technological developments in telecommunications and information technology following by cheaper costs make life easier on this planet. The impact is an increase in smartphone use among youth, they can take advantage of the positive side, but in developing countries the moreover most abusing and negative using.Purpose: To determine the mobile usage behavior-focusing on smartphone usage addiction among youth (15–24 years of age)Method: This study involves 107 respondents consisted of 55 males and 52 females with a youth average age is 15-24 years old. This study used a snowball sampling technique and the research instrument used the Addiction Rating Scale of Smartphone Usage Adapted from Smartphone Addiction Scale-Short Version (SAS-SV) taken by online questionnaire. The result is an addicted category when total score≥mean and not addicted when total score < mean Results: Finding that 53.3% of youth do not experience smartphone addiction and 46.7% of them have experience smartphone addiction. There is a relationship between economic status and smartphone addiction with a p-value of 0.005Conclusion: Finding that nearly half of the youth are addicted to smartphones, to pay the attention of parents and local psychological agencies to help them use them for positive purposes.